Divergent Functional Diversification Patterns in the SEP/AGL6/AP1 MADS-Box Transcription Factor Superclade. Issue 12 (7th October 2019) - Morel, Patrice; Chambrier, Pierre; Boltz, Véronique; Chamot, Sophy; Rozier, Frédérique; Rodrigues Bento, Suzanne; Trehin, Christophe; Monniaux, Marie; Zethof, Jan; Vandenbussche, Michiel
Abstract : Functional analysis of the petunia MADS-box gene SEP/AGL6/AP1 superclade compared to Arabidopsis and other species suggests major differences in the functional diversification of its members during evolution. Abstract: Members of SEPALLATA ( SEP ) and APETALA1 ( AP1 )/ SQUAMOSA ( SQUA ) MADS-box transcription factor subfamilies play key roles in floral organ identity determination and floral meristem determinacy in the rosid species Arabidopsis ( Arabidopsis thaliana ). Here, we present a functional characterization of the seven SEP / AGL6 and four AP1 / SQUA genes in the distant asterid species petunia ( Petunia × hybrida ). Based on the analysis of single and higher order mutants, we report that the petunia SEP1 / SEP2 / SEP3 orthologs together with AGL6 encode classical SEP floral organ identity and floral termination functions, with a master role for the petunia SEP3 ortholog FLORAL BINDING PROTEIN2 ( FBP2 ). By contrast, the FBP9 subclade members FBP9 and FBP23, for which no clear ortholog is present in Arabidopsis, play a major role in determining floral meristem identity together with FBP4, while contributing only moderately to floral organ identity. In turn, the four members of the petunia AP1 / SQUA subfamily redundantly are required for inflorescence meristem identity and act as B-function repressors in the first floral whorl, together with BEN / ROB genes. Overall, these data together with studies in other species suggest major differences in the functional diversification of the SEP / AGL6 and AP1 / SQUA MADS-box subfamilies during angiosperm evolution.